Symposium 3: Analysing and supporting the process of co-designing inquiry-based and technology-enhanced learning scenarios in higher education - Garcia, Iolanda; Barberá, Elena; Gros, Begoña; Escofet, Anna; Fuertes, Marc; Noguera, Ingrid; López, Marta; Cortada, Meritxell; Marimón, Marta (Proceedings of the International Conference on Networked Learning, 2014)
This paper is framed within a research project on the co-design of learning scenarios in higher education. Co-design is understood as a creative process developed collaboratively by teachers, students and researchers to design inquiry-based and technology-enhanced and networked learning scenarios. In this process, methods and instruments from the field of participatory design and learning design are used. Among other things, the co-design process involves discussing and negotiating the design principles to be used on a shared basis in order to devise the learning scenarios. These design principles are based on recent approaches to the model of inquiry-based and networked learning. The study applies the methodology of design-based research. The object of study is therefore the very process of co-designing, taking as key agents both the teachers and the students to whom those practices are addressed. A mixed approach is used for data collection, analysis and interpretation. It is the purpose of the research to develop instruments that support the co-design process and products through its representation and explanation. Several design tools and conceptual artefacts are used to guide practitioners in the creation of a common “language” and help them to reflect and to represent practice during the co-design process. Furthermore, a co-design methodology is proposed and applied in a cycle starting from the problematisation of the learning practice towards the creative envisioning of multiple solutions and the operationalisation of one of these solutions as a learning scenario. In particular the paper reports the first phase of the research which analyses the co-design work developed with a group of teachers from universities with two different models, one of them blended and the other virtual. Firstly, the theoretical framework is developed to highlight the theoretical and practical interactions between participatory design methods and tools and the domain of learning design. Secondly, the research design is described and a model is proposed for the analysis of the co-design process of inquiry-based and technology-enhanced and networked learning scenarios. To conclude, we discuss the major implications and challenges of this approach.